THE ROLE OF SOCIAL STEREOTYPES AND PSYCHOLOGICAL DEFENSE MECHANISMS IN THE FORMATION OF VICTIM BEHAVIOR IN WOMEN (International journal of artificial intelligence, 2026)
This article is devoted to the analysis of multi-factor socio-psychological determinants of the formation of victim behavior in women within the context of modern transformation processes. In the study, the image of the "traditional woman" in the national mentality is detailed as a surdogenic (inducing victimization) social attitude and a cognitive development factor that triggers the destructive development of the personality. Based on empirical data, the destructive functions of psychological defense mechanisms (denial, rationalization) activated under conditions of cognitive dissonance and their role in stabilizing the level of victimization are revealed. The article substantiates theoretical and experimental models of functional relationships between the susceptibility to socio-gender stereotypes and the victimization of personality behavior, and also proposes a system of psychological rehabilitation aimed at overcoming the "learned helplessness" syndrome in women.